INTELIGENCIA EMOCIONAL Y SOCIAL COMO FACTOR DE DESARROLLO INTEGRAL DEL TRABAJADOR EN GAMARRA - Tito Huamaní, Pedro Leonardo (2012)
The stresses of modern life, competition at the individual and business, the pressure of the clock, a constant demand for professional development, etc., Are situations that tend to alter the emotional state of most normal people, taking them to the edge of their own physical and mental limits. The result is often emotional imbalance. This imbalance not only affects the intimate life of a person, it affects their work and professional development, because emotions play an important role in the workplace. From anger to excitement, from frustration to satisfaction, every day we face-our own and others emotions. The key is to use emotions intelligently, to work for themselves, so help us control our behavior and our thoughts towards better results, which is known as emotional intelligence. The best way to define emotional intelligence is considered that this is the ability to apply awareness and sensitivity to discern the feelings underlying interpersonal communication, and to resist the temptation that leads us to react in an impulsive, thoughtless , instead working with responsiveness, with authenticity and sincerity. This is a problem that occurs in all areas, one of which has been more relevant in recent years is the workplace. But really the employers and workers give the necessary importance to this aspect? The study leads precisely to realize how important emotional intelligence as a development of the worker Peru, mainly in the business empire of Gamarra MSE, which allows us to have a broader picture of how they apply them, if so the case, emotional intelligence in their places of work and how it affects their performance